Die Strafbarkeit der Marktmanipulation unter dem europäischen Marktmissbrauchsregime - Richter, Thomas (Schriftenreihe zum deutschen, europäischen und internationalen Wirtschaftsstrafrecht, 2022)
This book examines the criminal liability for market manipulation pursuant to section 119 of the German Securities Trading Act (WpHG) under the European market abuse regime in force as of 2016. The changes in criminal liability brought about by European norms are analysed coherently. A legal comparison with EU countries reveals that the requirement of price impact is a special feature of the German offence. The book closely examines a new qualification of a crime, which raises unresolved questions as to its preconditions and has important consequences for criminal proceedings. Practising as a criminal defence lawyer, the author has a wealth of experience in capital markets criminal law and places particular emphasis on practical insights.